Effect of human urine enriched with Efficient Microorganisms on the yield of potato (Solanum tuberosum L.) Peruanita variety - Carbajal Mayhua, Rockmerd (2023)
This research was conducted in the community of Tranca Pampa- District of San Marcos de Rocchac, province of Tayacaja Department of Huancavelica, Peru; in the agricultural campaign 2019- 2020, with the objective of evaluating the effect of human urine enriched with efficient microorganisms on the yield of potato, peruanita variety. A randomized complete block experimental design with three replications was used to test the effect of 5 liters of urine plus EM, 10 liters of urine plus EM, 15 liters of urine plus EM and a witness without application. Plant height at 120 and 210 days, number, and weight of tubers per plant at harvest were evaluated. Analysis of variance and Duncan's multiple comparison tests of means at =0.05 were performed. The best yields were obtained with the application of 15 liters of urine plus EM (75.53 t ha-1) and 10 liters of human urine plus EM (73.48 t ha-1), significantly exceeding the other treatments; it is concluded that the application of liquid organic fertilizer based on human urine plus effective microorganisms contributes to a significant and favorable increase in the yield of the potato crop, Peruvian variety.